Relações de poder e educação: uma análise sobre o discurso de gênero e sexualidade no Brasil a partir da ADPF 457 do Supremo Tribunal Federal - Assis, Taíza Soares (2021)
The purpose of this study is to investigate the dimension that the discourse on gender and sexuality issues occupies at school, as well as understand how the theme has been treated in the judiciary, especially in the Federal Supreme Court, based on the analysis of the Allegation of Non-Compliance with a Fundamental Precept - ADPF 457. By understanding that society is formed by a complex of forces that struggle daily to exercise power and that speeches are important instruments for the construction and maintenance of truths, as a methodology, the research uses the discourse analysis method, proposed by Foucault, in order to understand how discourses on gender and sexuality are located within the strategic system of power that makes up society, especially in the educational and judicial sphere. Furthermore, it is an exploratory research, which uses a bibliographic and documentary method, as it has its theoretical basis based on the consultation in books, scientific articles, and academic works on the subject, in addition to proceeding with the analysis of a legal document, that is, the judgment handed down in ADPF 457. Initially, the work immerses in Foucault's studies on the relations of power and truth, in order to understand how sexuality was used as a device to control bodies and manage the lives of populations, with emphasis on the role of the school as a disciplinary institution responsible for formal education. The text also seeks to investigate how the same device of sexuality influenced the formation of an anti-gender discourse, which boosted the creation of the expression “gender ideology”. Secondly, the research seeks to deepen study on education and its role in society, to then understand why the school has become this important debate stage about conflicts involving gender and sexuality and how it can influence the way of learning these categories. Finally, the third part of the research seeks to deepen the analysis of discourse of Foucault, as a methodological resource to analyze legal practices, specifically, the judgment produced in the ADPF 457, to then understand the role of the Supreme Court in the construction of discourses on gender and sexuality in education and, consequently, in the creation of the supposed truths of these categories. As a result, it is concluded that, as the discourse is a source of power, discourses on gender and sexuality must be appropriated, fighting so that the right to education is not used as a pretext to impose moralization and standardization ideals. Discourse is a practice capable of creating materiality and, therefore, should be seen as a weapon to combat the various forms of misinformation, discrimination and prejudice.